Characterization of the use of psychoactive substances used by truck drivers traveling on a section of BR-010, in the state of Maranhão, Brazil - Belfort, Marcia Guelma Santos; Silva, Cianny Ximenes Rodrigues; Nunes, Sheila Elke Araújo; Sallet, Lunalva Aurelio Pedroso; de Sousa , Marcos Jean Araújo; da Silva, Síria Alcantara (Seven Editora, 2023)
Truck drivers play a fundamental role in the economic development of the entire country by transporting essential elements to supply cities, such as food. As a result, these drivers suffer a lot of pressure and stress for the arrival of these loads and therefore feel the need to drive without stopping or resting, being led to use psychoactive drugs to stay awake and endure the long workday. In view of this, this work aims to identify the consumption of licit and illicit drugs among truck drivers who travel along the BR-010 stretch in municipalities in the Tocantina region and to investigate the drugs most used by truck drivers. For this, a descriptive and exploratory research was used, a field research with the application of a form with semi-structured questions, carried out in two gas stations located in the city of Imperatriz-MA. Twenty (100%) male truck drivers were analyzed, with an average age of 22 to 70 years, working in this profession for 18.34 years and driving about 16.3 hours a day. Among the drugs, the most used was alcohol, being ingested by 95% (19) of those analyzed, followed by rivet with 55% (11), cocaine 50% (10) and marijuana 35% (7), ecstasy 20% ( 4), morphine 10% (2) and heroin 10% (2). The main reason for consuming these substances was to stay awake 40% (8). With this, there is a need to implement public policies with a multidisciplinary team to make truck drivers aware of the risks that the use of these drugs can cause to their health and, even, put the lives of other people in danger through traffic accidents.DOI: https://doi.org/10.56238/devopinterscie-006